Wind potential investigation with turbine siting control for improved energy yield at El-Tor Region, Egypt. (May 2022) - Ramadan, Haitham S.; Abdelrahman, Mohamed A.; Sharaf, Adel M.
Highlights : State-of-the-art of the wind resource assessment and optimal/control wind turbine micro-siting. Analysis of wind data characteristics and the regional topographical data of El-Tor, Egypt. Wind resource assessment for El-Tor region to evaluate the wind energy yield potential. Controlled wind turbines optimal layout in the site after type selection. Cost benefit analysis of the wind farm design considering different different uncertainties/loans. Abstract: The paper presents a detailed study of wind farm sizing/siting at Egypt, EL-Tor Sinai Peninsula. The study is driven by the ongoing Egyptian clean energy policy to utilize wind energy a viable source of renewable electricity within the national new planned energy-mix generation. The wind ample coastal/desert resources in Egypt stimulated the Government of Egypt to initiate the wind expansion program policy in October 2014 using wind and solar/PV renewable sources through the Feed-In Tariff incentive program to be one of the African and Middle Eastern pioneer countries reaching 20% of renewable energy (RE)-based electricity generation by 2022 and reducing the fossil fuel dependency. After presenting the techno-economic investigations of large wind farms in El-Tor area located in Sinai Peninsula of Egypt, the state of the art of defining the near-optimal wind micro-siting of best controlled wind turbines and the relevant technical selection criteria are introduced. The topographical data and wind characteristics in El-Tor area are fully analyzed. Using the WindPRO TM software, the wind site optimal selection of controlled wind turbines and layout for maximum energy production are discussed considering the governing risk uncertainties; then finalized in terms of cost-benefit feasibility study during the wind farm life span for the national grid integration. Considering the soft and commercial loan factors, the economic viability of the wind farm implementation with its controlled turbine locations/spacing in El-Tor area is studied in comparison with the conventional power plants neglecting the certified emission reductions benefit. The methodology of this paper illustrates a systematic guided way for the selection and sizing of large wind farms as either standalone with storage battery systems or gas turbine back up or direct interfacing with the electric utility at high penetration levels of 15-20%. Graphical abstract: Image, graphical abstract